Evaluating the link between immune characteristics and attention deficit hyperactivity disorder through a bi-directional Mendelian randomization study - Jue, Hu; Dan-fei, Chen; Fang-fang, Li; Ke-pin, Yu; Jia-ye, Xu; Hui-ting, Zhang; Xiao-bo, Xuan; Jian, Chen (Frontiers in Immunology, 2024)
Context: Despite the recognition of ADHD as a multifaceted neurodevelopmental disorder, its core causes are still ambiguous. The objective of this study was to explore if the traits of circulating immune cells contribute causally to susceptibility to ADHD.Methods: By employing a unified GWAS summary data covering 731 immune traits from the GWAS Catalog (accession numbers from GCST0001391 to GCST0002121), our analysis focused on the flow cytometry of lymphocyte clusters, encompassing 3,757 Sardinians, to identify genetically expected immune cells. Furthermore, we obtained summarized GWAS statistics from the Psychiatric Genomics Consortium to evaluate the genetic forecasting of ADHD. The studies employed ADHD2019 (20,183 cases and 35,191 controls from the 2019 GWAS ADHD dataset) and ADHD2022 (38,691 cases and 275,986 controls from the 2022 GWAS ADHD dataset). Through the examination of genome-wide association signals, we identified shared genetic variances between circulating immune cells and ADHD, employing the comprehensive ADHD2022 dataset. We primarily utilized inverse variance weighted (IVW) and weighted median methods in our Mendelian randomization research and sensitivity assessments to evaluate diversity and pleiotropy.After adjusting for false discovery rate (FDR), three distinct immunophenotypes were identified as associated with the risk of ADHD: CD33 in Im MDSC (OR=1.03, CI: 1.01~1.04, P=3.04×10 -5 , PFDR=0.015), CD8 br NKT %T cell (OR=1.08, 95%CI: 1.04~1.12, P=9.33×10 -5 , PFDR=0.023), and CD8 br NKT %lymphocyte (OR=1.08, 95%CI: 1.03~1.12, P=3.59×10 -4 , PFDR=0.066). Furthermore, ADHD showed no statistical effects on immunophenotypes. It's worth noting that 20 phenotypes exist where ADHD's appearance could diminish 85% of immune cells, including FSC-A in myeloid DC (β= -0.278, 95% CI: 0.616~0.931, P=0.008), CD3 in CD45RA-CD4+ (β= -0.233, 95% CI: 0.654~0.960, P=0.017), CD62L-monocyte AC (β=0.227, 95% CI: 0.038~1.518, P=0.019), CD33 in CD33 br HLA DR+ CD14dim (β= -0.331, 95% CI: 0.543~0.950, P=0.020), and CD25 in CD39+ resting Treg (β=0.226, 95% CI: 1.522, P=0.022), and FSC-A in monocytes (β= -0.255, 95% CI: 0.621~0.967, P=0.234), among others.Studies indicate that the immune system's response influences the emergence of ADHD. The findings greatly improve our understanding of the interplay between immune responses and ADHD risk, aiding in the development of treatment strategies from an immunological perspective.